Self-reported food allergy and its clinical significance in adult bronchial asthma patients:– A prospective study - Priya Sharma; Bharath Janapati; Rachna Rohatgi; Anil Kumar Jain (Indian Journal of Allergy Asthma and Immunology, 2021)
BACKGROUND: Self-reported food allergy is very common in asthmatics and hence these food items are frequently avoided by the patients. Food allergy is defined as an adverse immunological response to a dietary protein. Skin prick test (SPT) is a sensitive tool for identifying the presence of specific immunoglobulin E antibodies that can be associated with acute allergic reactions. However, sensitization often exists without clinical consequences, and at the same time, self-reported food allergens are frequently negative on SPT. The purpose of our study was to assess the clinical relevance of self-reported food allergy and the role of SPT in identifying food allergies in patients with bronchial asthma. METHODOLOGY: One hundred bronchial asthma patients were screened for this study, and skin prick testing for 22 food allergens frequently consumed in India, particularly Northern India was performed. RESULTS: A total of 36 subjects reported perceiving precipitation or an increase in severity of the asthmatic symptoms by one or more food items, and the most common food items mentioned in history were curd in 24%, rice in 19%, citrus fruits such as lemon in 14%, orange in 14%, banana in 8%, cold drinks in 16%, and ice creams in 16%. There were 68 patients negative for food allergens by SPT (food allergen negative [FAN] group) and 32 patients were positive (Food allergen Positive [FAP] group). Out of 36 asthmatics with self-reported food allergy, none was found to be SPT positive to the reported food allergens. However, 50% of patients with self-reported and only 21.9% with no history of food allergy were positive to one or more food allergens. Further, FAP group patients were tolerating these foods without any trouble or exacerbation of symptoms. Among the FAP group, 96.9% of patients had positive SPT for one or more other allergens also such as insects, pollens, fungi, or other aeroallergens. Only one patient had isolated food allergy by SPT. It implies that isolated food allergy is very rare in asthmatic patients. Common food allergens found positive by SPT were black gram in 12%, followed by red gram 9% and bengal gram, rice, and Baker's yeast 7% each. CONCLUSION: We concluded that the prevalence of food allergy in India among asthmatic adults though high, has a very poor correlation between patient's history of food allergens that is perceived as a precipitating or exaggerating factor for symptoms and actual sensitization as elicited by SPT. At the same time, there is high nonspecific food sensitization in self-reported patients as compared to those with no history of any perceived food allergy.